2015
DOI: 10.1002/maco.201408211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of corrosion behavior of Al‐Mn and Al‐Mg alloys in chloride aqueous solution

Abstract: The microstructure and corrosion behavior of Al‐Mn alloy 3A21 and Al‐Mg alloy 5A05 in 3.5% NaCl solution were examined and compared. The results of the microstructure survey performed by optical microscope confirm the inhomogeneous nature of the intermetallic particles of the two alloys. The X‐ray diffraction (XRD) analysis reveals the presence of intermetallic Al6Mn and Al6(FeMn) particles in the 3A21 alloy and Al3Mg2, Mg2Si and FeAl3 particles in the 5A05 alloy, respectively. Electrochemical results, in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The E CORR for Al‐5.5Mn was unstable over the first 3 h of exposure to 0.138 M MgCl 2 and throughout the 12 h exposure to 0.275 M NaCl. The potential transients suggest local metastable breakdown events, possibly associated with Mn‐depleted Al‐enriched regions of the alloy , which was observed recently on Al‐Mn alloys . Similar metastable events were not observed in E CORR measurements on Al‐13.5Mn.…”
Section: Discussionsupporting
confidence: 85%
“…The E CORR for Al‐5.5Mn was unstable over the first 3 h of exposure to 0.138 M MgCl 2 and throughout the 12 h exposure to 0.275 M NaCl. The potential transients suggest local metastable breakdown events, possibly associated with Mn‐depleted Al‐enriched regions of the alloy , which was observed recently on Al‐Mn alloys . Similar metastable events were not observed in E CORR measurements on Al‐13.5Mn.…”
Section: Discussionsupporting
confidence: 85%
“…As discussed above, E ptp is independent with ex‐situ applied load, E rev , and scan circle. Previous literature also reported that E ptp is independent with surface orientation, i rev , pH, and immersion time . These factors can hugely affect the corrosion degree and surface morphology of alloys.…”
Section: Discussionmentioning
confidence: 88%
“…These factors can hugely affect the corrosion degree and surface morphology of alloys. Also, factors like pH, ex‐situ applied load, and immersion time could significantly influence pitting potential E pit . The value of E pit showed negative trend with pH and applied load.…”
Section: Discussionmentioning
confidence: 99%
“…Aluminium-magnesium (Al-Mg) alloys are attractive for their high strength, high ductility, high formability, high corrosion resistnace and weldablity [1,2]. Various methods are applied to increase the strength and other properties by modifying the structures of Al-Mg alloys [3].…”
Section: Introductionmentioning
confidence: 99%